Answer:
The answer is
![x = ( - 5 + √(13) )/(6) \: \: \: \: or \: \: \: x = ( - 5 - √(13) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/mhvnyvq8b1fbhg03x8vararndb09titgol.png)
Explanation:
2x² = - x² - 5x - 1
Rearrange the terms and simplify
That's
2x² + x² + 5x + 1 = 0
3x² + 5x + 1 = 0
Using the quadratic formula solve the equation
That's
![x = \frac{ - b\pm \sqrt{ {b}^(2) - 4ac} }{2a}](https://img.qammunity.org/2021/formulas/mathematics/high-school/qeco2a1u6dnwga0e3z5q16k2dquu8gh96d.png)
From the question
a = 3 , b = 5 , c = 1
So we have
![x = \frac{ - 5\pm \sqrt{ {5}^(2) - 4(3)(1) }}{2(3)} \\ = ( - 5\pm √(25 - 12) )/(6) \\ = ( - 5\pm √(13) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/woduq1266igaqiy7p5h63b7ar5s6holyx9.png)
We have the final answer as
![x = ( - 5 + √(13) )/(6) \: \: \: \: or \: \: \: x = ( - 5 - √(13) )/(6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/mhvnyvq8b1fbhg03x8vararndb09titgol.png)
Hope this helps you